Efficacy of Intravitreal Injection of Filtered Modified Low-Dose Triamcinolone Acetonide and Ranibizumab on Pseudophakic Cystoid Macular Edema - Tariq, Farheen; Wang, Yanfen; Ma, Bo; He, Yidan; Zhang, Shu; Bai, Ling (Frontiers in Medicine, 2022)
Purpose: To compare the visual and morphological effects between intravitreal injection of filtered modified 2mg triamcinolone acetonide (TA) and 0.5mg Ranibizumab in patients with pseudophakic cystoid macular edema (PCME). Methods: A retrospective, interventional study was conducted from January 2015 to February 2020 involving patients with PCME after uneventful cataract surgery. Twenty-five patients (25 eyes) with PCME received an intravitreal injection of 0.22μm filtered modified 2mg TA, while fifteen patients (15 eyes) received 0.5mg ranibizumab injection. Central macular thickness (CMT), best-corrected visual acuity (BCVA), intraocular pressure (IOP), times of repeated injections and other side effects were observed at 2 weeks, 1 month, 3 months, and 6months after injection, then the data were compared with pre-injection information in each group and between the two groups. Results: Both TA and ranibizumab intravitreal injection can achieve improved BCVA and reduced CMT in patients with PCME(P<0.05)., with a trend towards greater improvement in the TA group, but the difference was only significant at 3 months (P<0.05). IOP was in the normal range without any significant difference (P>0.05). 33% of patients in the ranibizumab group required repeated intravitreal injection compared to 4% in the TA group. Further stratified analysis showed that the better therapeutic effect of TA group at 3 months after injection only existed in patients with diabetes mellitus (DM), while not in patients without DM. There was no repeat injection in the TA group and 12.5% in the ranibizumab group for patients without DM, while 16.7% in the TA group and 57.1% in the ranibizumab group required repeated injection for patients with DM, which had a significant difference (P<0.05). Conclusion: Intravitreal injection of filtered modified 2mg TA is safe, effective and an inexpensive alternative to anti-vascular endothelial growth factor (anti-VEGF) agents for patients with PCME, especially for patients concurrently with DM. A large number of clinical randomized controlled studies along with long-term follow-up observations are needed.